1998
DOI: 10.1097/00000441-199808000-00003
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand Disease: Recent Advances in Pathophysiology and Treatment

Abstract: This review focuses on new developments in the pathophysiology and treatment of von Willebrand disease (vWd). New aspects of the cell biology, gene control, and structure-function correlates of von Willebrand factor (vWf) are reviewed. vWd is more prevalent than previously recognized, affecting up to 1% of the population; this is particularly evident in women's health. Blood group is an important determinant of von Willebrand factor levels; individuals of blood group O tend to have lower plasma levels of vWf t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…From the amino-terminal end to the carboxyl-terminal end, the structure of the VWF monomer includes the FVIII binding domain, the A1 loop that binds to platelet GPIb, the VWF cleaving protease sensitive site, the A3 loop that binds collagen, and the RGD sequence that binds platelet GPIIb/IIIa [5]. A and B blood group sugars are covalently linked to VWF [6] in proximity to the A1 domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the amino-terminal end to the carboxyl-terminal end, the structure of the VWF monomer includes the FVIII binding domain, the A1 loop that binds to platelet GPIb, the VWF cleaving protease sensitive site, the A3 loop that binds collagen, and the RGD sequence that binds platelet GPIIb/IIIa [5]. A and B blood group sugars are covalently linked to VWF [6] in proximity to the A1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main collagen binding activity takes place at the A3 domain [5], lower CBA values have also been found in blood group O samples when compared to blood groups A, B, and AB in an earlier study [8], but because of the small number of samples, statistical significance was previously not achieved [8]. Our study confirms these findings with statistical significance; however, the mechanism appears likely to be different from that causing lower RCoF values [7].…”
Section: Discussionmentioning
confidence: 99%
“…2 Among three types of von Willebrand disease, type 1 is the most commonly seen type, while type 3 is the least common and the most severe type. 7 Our patient was diagnosed to have von Willebrand disease type 3 during evaluations carried out for epistaxis episodes when she was 18 months old.…”
Section: Commentmentioning
confidence: 94%
“…The biological rationale of our findings is uncertain. Nevertheless, coagulation defects have been repeatedly associated with cardiovascular risk [26] and several studies have found an association between coagulation factors and ABO blood group [27,28]; even a significant interaction of factor VIII activity, age and ABO phenotypes has been reported [29]. It has also been suggested that ABO phenotypes differ with respect to serum lipids [30] and even height.…”
Section: Biological Mechanismsmentioning
confidence: 99%